2019
DOI: 10.1101/635383
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular basis for dyneinopathies reveals insight into dynein regulation and dysfunction

Abstract: Cytoplasmic dynein plays critical roles within the developing and mature nervous systems, including effecting nuclear migration, and retrograde transport of various cargos. Unsurprisingly, mutations in dynein are causative of various developmental neuropathies and motor neuron diseases. These "dyneinopathies" define a broad spectrum of diseases with no known correlation between mutation identity and disease state. To overcome complications associated with studying dynein function in human cells, we employed bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…We find intermittent increases in velocity, resulting in frequency distributions with long tails (Figure 4h,k). The ranked velocities of SPB‐M and SPB‐D both suggest velocities ranging from 4.5 to 27 nm/s, more comparable to those reported in literature (Marzo et al, 2019; Moore et al, 2009; Omer et al, 2020).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We find intermittent increases in velocity, resulting in frequency distributions with long tails (Figure 4h,k). The ranked velocities of SPB‐M and SPB‐D both suggest velocities ranging from 4.5 to 27 nm/s, more comparable to those reported in literature (Marzo et al, 2019; Moore et al, 2009; Omer et al, 2020).…”
Section: Resultssupporting
confidence: 88%
“…In order to estimate the forces driving the movement of the nucleus during mitosis, we follow the mobility of the SPBs that move to the diametrically opposite poles of the nucleus (Knop et al, 1997;Seybold & Schiebel, 2013) comparable to those reported in literature (Marzo et al, 2019;Moore et al, 2009;Omer et al, 2020).…”
Section: In Vivo Spb Motility In Mitotic Cells and Minimal Force Of Pulling The Nucleusmentioning
confidence: 99%
“…Spindle tracking was performed on maximum intensity projections (XY) using a custom written MATLAB routine (as described previously 76 ). Dynein-mediated spindle movements were manually selected from the tracking data to obtain the various metrics described in Figures 4B -E, and 5B -E. To determine the fraction of time the spindle centroid resides within 1 µm of the cell cortex ( Figures 4F and 5F), an additional MATLAB routine was generated with which the user manually defines the cell cortex of the mother and bud cell.…”
Section: Spindle Tracking and Statistical Analysismentioning
confidence: 99%
“…Possible causes of the high incidence of mental disorders in SLE patients include long‐term GCs use, psychological pressure, and recurrent symptoms 15 . Dynein plays a vital role in the development of neurons, such as neuronal migration and neuronal regeneration 16 17 …”
Section: Introductionmentioning
confidence: 99%